2015
DOI: 10.1038/ncomms9728
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane protein sorting driven by membrane curvature

Abstract: The intricate structure of prokaryotic and eukaryotic cells depends on the ability to target proteins to specific cellular locations. In most cases, we have a poor understanding of the underlying mechanisms. A typical example is the assembly of bacterial chemoreceptors at cell poles. Here we show that the classical chemoreceptor TlpA of Bacillus subtilis does not localize according to the consensus stochastic nucleation mechanism but accumulates at strongly curved membrane areas generated during cell division.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 65 publications
4
49
0
Order By: Relevance
“…Recent work in B. subtilis with the chemoreceptor TlpA, which also forms ToDs, suggested that curvature sensitivity arises from rigidity within the ToD cone shape holding the transmembrane domains apart and at an angle in the membrane23. The researchers reported that curvature sensitivity was eliminated by the introduction of two glycine residues within the receptor HAMP domain, increasing receptor flexibility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in B. subtilis with the chemoreceptor TlpA, which also forms ToDs, suggested that curvature sensitivity arises from rigidity within the ToD cone shape holding the transmembrane domains apart and at an angle in the membrane23. The researchers reported that curvature sensitivity was eliminated by the introduction of two glycine residues within the receptor HAMP domain, increasing receptor flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…This ToD geometry led Endres22 to propose a curvature-based mechanism for polar localization of the array. Recent work in Bacillus subtilis supported this notion, concluding that TlpA, which is homologous to E. coli chemoreceptors, is sorted by membrane curvature23.…”
mentioning
confidence: 93%
“…Furthermore, although the AtKEA2 protein without the N-terminal domain constitutes an active antiporter (Aranda-Sicilia et al, 2012), it fails to complement the growth defects of the double mutant plant, suggesting that the specific localization of the protein is crucial for its function. The association of oligomers of AtKEA2 could depend on membrane tension or curvature, which is highest at the poles but more relaxed at the midcell, as in bacteria (Laloux and Jacobs-Wagner, 2014;Strahl et al, 2015).…”
Section: The Long N-terminal Domain Attaches Atkea1/2 To Specific Locmentioning
confidence: 99%
“…During cell division, the region at which the division septum meets the lateral edge can display high two-dimensional concave curvature. Several reports have identified concave membrane curvature as a beacon that recruits certain shape-sensing proteins to reside preferentially at the poles, division septum, or along the lateral surface (Govindarajan et al, 2013; Lenarcic et al, 2009; Ramamurthi and Losick, 2009; Renner et al, 2013; Strahl et al, 2015; Ursell et al, 2014). …”
Section: Introductionmentioning
confidence: 99%